A Synthetic Acetylation Substrate to Study Gcn5 Targeting and Function in Yeast. - Rossl, Anthony (Université d'Ottawa / University of Ottawa, 2018)
Acetylation was previously thought to occur exclusively on histones, but recent high-throughput screens have identified thousands of non-histone substrates. Despite the identification of these sites, little is known about how these acetyltransferase enzymes target their substrates. Gcn5 is the catalytic acetyltransferase found within the highly conserved SAGA complex. Recently, a member of this complex, Ada2, was found to impact Gcn5 substrate selection. In the yeast model organism Saccharomyces cerevisiae, a synthetic substrate developed from a proposed Gcn5-specific consensus sequence is used to identify regulators of Gcn5 substrate selection. This work is the first to demonstrate that addition of a consensus sequence is enough to confer acetylation of a non-substrate. With this method, Ada3 was identified as a key regulator, and acetylome profiling identified novel targets for Gcn5 dependent acetylation specifically regulated by Ada3. This system could be adapted for other acetyltransferases to identify regulators of substrate selection.
Keywords: Gcn5; Acetylation; Targeting; Consensus sequence; Ada3; SILAC; SAGA; Sirtuin